A new morphologically cryptic species of Phyllomedusa (Anura: Phyllomedusidae) from Amazonian forests of northern Peru revealed by DNA sequences - Castroviejo-Fisher, Santiago; Köhler, Jörn; Riva, Ignacio De La; Padial, José M. (Zootaxa, 2017)
We describe and name Phyllomedusa chaparroi sp. nov., a medium-sized species (snout–vent length in adult males 67.9–77.5 mm) of monkey frog from Amazonian rainforests of northern Peru. Although morphologically most similar to P. boliviana and P. camba (indistinguishable from the latter in external qualitative and quantitative traits), phylogenetic analysis of combined mitochondrial and nuclear markers place the new species sister to a clade containing P. neildi, P. tarsius, and P. trinitatis. Phyllomedusa chaparroi can be readily differentiated from these species by having a dark reddish-brown iris with indistinct tiny orange spots versus an orange iris with marked dark reticulation found in P. neildi, P. tarsius, and P. trinitatis. Furthermore, genetic distances for a 532 bp sequence of the 16S gene between the new species and its sister species are 2.8–4.1 %, whereas distances are 4.5–5.5 % to the morphologically cryptic P. camba. We briefly discuss the importance of DNA sequences in revealing morphologically cryptic species and modify the content of the P. tarsius species group based on phylogenetic analyses and observations on iris coloration.